The deadly gifts of livestock: Zoonoses - Grace, Delia (2012)
In this paper the author briefly discusses the history of how livestock diseases were transmitted to humans as early as the time of hunting to the time improved agriculture farming. Highlights of the paper focused on the so called classical zoonoses : neglected diseases on neglected populations. The author concludes by stating the current practices in managing zoonoses as well as on its management in the future.